2019
DOI: 10.3390/jcm8030407
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Use of Eculizumab in Pregnancy and Complement Activation–Associated Diseases Affecting Maternal, Fetal and Neonatal Kidneys—The Future Is Now?

Abstract: Excessive complement activation is involved in the pathogenesis of many diseases and the kidney is an organ with particular susceptibility to complement-mediated injury. Apart from paroxysmal nocturnal hemoglobinuria (PNH) and atypical hemolytic uremic syndrome (aHUS), there are several other diseases with clear evidence of complement activation affecting both maternal and fetal kidneys during pregnancy and causing long-term adverse outcomes. Several novel drugs have been recently developed for blocking the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 95 publications
(152 reference statements)
0
37
0
2
Order By: Relevance
“…Our patient had a spontaneous pregnancy during maintenance Eculizumab treatment with normal fetal development, complicated by pre-eclampsia by week 20 of gestation and aHUS relapse at week 26 of gestation. A form of pre-eclampsia with severe features and HELLP syndrome were considered the differential diagnosis [16,17]; nevertheless, the previous history of aHUS and the absence of elevation of ALT/AST enzymes oriented the diagnosis towards an aHUS relapse. She had several risk factors for the development of pre-eclampsia, namely pre-existing hypertension [18] and chronic kidney disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had a spontaneous pregnancy during maintenance Eculizumab treatment with normal fetal development, complicated by pre-eclampsia by week 20 of gestation and aHUS relapse at week 26 of gestation. A form of pre-eclampsia with severe features and HELLP syndrome were considered the differential diagnosis [16,17]; nevertheless, the previous history of aHUS and the absence of elevation of ALT/AST enzymes oriented the diagnosis towards an aHUS relapse. She had several risk factors for the development of pre-eclampsia, namely pre-existing hypertension [18] and chronic kidney disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…An ambiguous role is played by drugs administered to preterm and low birth weight babies. The therapeutic benefit of drugs is balanced against the frequently unknown nephrotoxic potential [12][13][14][15].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…48 There are multiple cases of normal complement levels in exposed newborns. 47,49,50 It has also been suggested that low complement levels may be related to prematurity associated with the underlying disease. 51,52 Further data are needed to conclusively determine whether this drug is safe to be used during pregnancy.…”
Section: Hyperhemolysis Prophylaxismentioning
confidence: 99%